(untitled) (South East Asia Journal of Public Health, 2013)
Anemia is a serious public health concern in most developing countries and the prevalence of anemia is quite high among adolescent girls. A cross-sectional descriptive study was carried out among school going adolescent girls in urban as well as rural schools of the Lucknow district, Uttar Pradesh, India from October 2008 to September 2009 with the objectives of studying the prevalence of anemia and the various socio-demographic characteristics in relation to anemia. Multistage random sampling was used to select the requisite number of girls. A total of 847 school going adolescent girls between 10-19 years of age were interviewed. Information regarding their socio-demographic characteristics was collected and the girls were also examined for presence or absence of pallor for anemia. Statistical analyses were done using percentage, Chi-square test, and odds ratio. The prevalence of anemia was found to be 55.6% and 57.9% in urban and rural school going adolescent girls respectively and significant association of anemia was observed with religion, caste and socio-economic status (p value<0.05). There is need to develop strategies for intensive adult education, nutrition education and dietary supplementation including anemia prophylaxis. South East Asia J Public Health | Jan-June 2012 | Vol 2 Issue 1 | 8-12 DOI: http://dx.doi.org/10.3329/seajph.v2i1.15254